Korelasi Pemikiran Kebangsaan Sartono Kartodirdjo Terhadap Konsep Politik Inspiratif Mahfud MD Perspektif Teori Strukturasi - Amin, Sifaul (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
Creating an advanced nation cannot be separated from the role of revolutionary and adaptive thinking of national figures. Sartono Kartodirdjo, as one of the senior historians in Indonesia, is famous for his thoughts and ideas, including the key to creating a developed nation. Sartono Kartodirdjo has the idea that in creating a developed and modern country, there are five principles of life that must always be applied. The five principles are unity and integrity, freedom and liberty, equality, identity and culture (personality), and work ethic (performance). In contrast to Sartono Kartodirdjo, Mahfud MD, as a national figure who currently still exists on the national stage, has ideas about inspirational political concepts that are in line with Sartono Kartodirdjo's thoughts. Inspirational politics is politics that builds justice, law enforcement, equality and elects fair and honest leaders. The correlation and relevance of the thoughts of these two figures is important to study and apply in order to achieve common national goals. This research is qualitative research that is descriptive qualitative analytical with a sociological approach. This research concludes that there is a close correlation and connection between Sartono Kartodirdjo's thoughts about the five principles of life to create an advanced nation and Mahfud MD's thoughts about inspirational politics. The thoughts of these two figures are also relevant to the current condition of the Indonesian nation which requires united efforts to realize the nation's ideals of becoming a developed nation. Keywords: Thought; Sartono Kartodirdjo; Mahfud MD's Inspirational Politics; Structuration